Venstreorienterede der blev højreorienterede uden at vide det - Dyrberg, Torben Bech (Politik, 2013)
In the article I argue that today’s Left has adopted several characteristics, which used to identify the reaction- ary right. e basic reason is that since the late 1940s it has gradually adopted a culturalist outlook and thus turned against the Enlightenment tradition. I locate 6 shifts in the last 7 decades, which come in pairs. e critique of modernity and the irt with conservative anti-imperialism in the late 1940s; the anti-authoritarian critique and the resentment against post-scarcity society and the anti-imperialism in the rst post-trend in the 1960/70s; and the disillusioned relativism and multiculturalism of the second post-trend in the 1980/90.